Issues in the Recognition versus Disclosure of Financial Information Debate - Novak, Aleš (Naše gospodarstvo/Our economy, 2016)
Empirical evidence from the academic literature on capital market effects of financial information placement (i.e., recognition on the face of the primary financial statements versus disclosure in the notes to the financial statements) is not straightforward. Therefore, the purpose of this paper is to contribute to the recognition versus required disclosure debate in a standard-setting context by exploring possible reasons for perceived differences between recognized and disclosed amounts. These differences, in our view, arise due to demonstrated auditors’ greater tolerance for misstatement in disclosed amounts, allowed non- compliance with disclosure requirements even in strong enforcement regimes, lesser care that preparers of financial statements devote to disclosures relative to recognized items as well as behavioural factors and differential processing costs related to the users of financial information. We believe that these arguments strengthen the case for the general preference for the recognition of financial information in the standard-setting context. The original scientific contribution of this paper is to systematically identify the reasons for the differences between recognized and disclosed amounts in financial statements. As such, this paper may provide a suitable basis for the justification of certain conceptual changes in the field of international accounting standards that are currently underway.